Pesquisa da própria prática ao ensinar matemática: uma análise de estratégias de resolução de problemas com estudantes do 5º ano de uma escola do campo - BARREIRA, Jonas Souza (Universidade Federal do Pará, 2020)
This study aims to investigate the way in which the teacher practices contributes to the 5th year students of a field school, which are strategies to solve addictive problems. It is a research of the practice itself, as a research methodology, which includes the perspective of Qualitative Research in Mathematical Education, for which the researcher teacher assumes a double role: the teacher who teaches mathematics to students in the field and the researcher of his own practice. It had as a theoretical reference the theory of the reflective teacher combined with problem solving, such as the possibilities of improving the teaching of mathematics and a reflective practice of the teacher who teaches mathematics. A research took place in the first semester of 2019, in a class from the 5th year of elementary school in a field school, located in a campaign community in the region of Marabá, southeastern Pará. The instruments used were the field diary of the researcher teacher, the student notebooks and the transcripts of the audios of the lessons recorded during an observation. The results show that students also learn built for school to learn mathematicians, thereby building new strategies for solving mathematical problems. Still, that a mediation teacher through dialogues with students allows for more interactive and interactive classes, as it allows students to expose their thoughts and share their problem solving strategies. It is understood with this that the teacher needs to cancel a teaching practice based only on the use of instructional rules and methods, it is necessary to diversify or teach how to give a voice to the student, with no sense of not listening for himself, for his colleagues and for the teacher , realizing knowledge that the student carries as an important epistemological baggage for the teaching of mathematics and what are the valuable knowledge as essential for the process of teaching and learning mathematical content.